Tingkat keberhasilan reklamasi lahan bekas tambang batubara pada PT Bukit Baiduri Energi Kabupaten Kutai Kartanegara kota Samarinda Kalimantan Timur - Aipassa, Marlon Ivanhoe; Zainuddin, Zainuddin; Hasan, Harjuni (Dinamika Lingkungan Indonesia, 2020)
Kartanegara Regency and Samarinda City East Kalimantan. From the results of the research and evaluation of the reclamation plan documents and RKTTL, as well as the reclamation implementation report, the Backfilling plan for 2017 is 35.80 Ha and is realized at 22.36 Ha, so that the percentage of success rates reaches 62,46%. The land management and land revegetation plan for 2017 is 62.12 Ha and is realized at 10.26 Ha, so that the percentage of success rate is 16.52%. Revegetation of PT BBE land for the last 3 (three) years from 2015-2017 with a plan of 165.17 Ha and realized as much as 129.05 Ha, resulting in a percentage of success rate of 78.13%, but when compared with the total realization of reclamation (land arrangement ) amounting to 109.06 Ha, realization of revegetation 129.05 Ha, then the success rate of revegetation of reclaimed land is 118.33%. This shows that PT BBE's commitment to environmental management is quite good. Based on the results of laboratory analysis, water quality at all outlet points of PT BBE compliance still meets environmental quality standards of pH 6-7 (BML 6-9). While the soil quality of top soil does not meet environmental quality standards (soil pH 3.68). Based on the overall evaluation results, the percentage of successful reclamation implementation at PT BBE is 78.43% (categorized as moderate).